Digital health technology derived measures: Biomarkers or clinical outcome assessments? - Elena S. Izmailova; Charmaine Demanuele; Marie McCarthy (Wiley, 2023)
Abstract Digital health technologies (DHTs) present unique opportunities for clinical evidence generation but pose certain challenges. These challenges stem, in part, from existing definitions of drug development tools, which were not created with DHT‐derived measures in mind. DHT‐derived measures can be leveraged as either clinical outcome assessments (COAs) or as biomarkers since they share properties with both categories of drug development tools. Examples from the literature indicate a variety of applications for DHT‐derived data, including capturing disease physiology, symptom tracking, or response to therapies. The distinction between the categorization of DHT‐derived measures as COAs or as biomarkers can be very fine, with terminology variability among regulatory authorities. This has significant implications for integration of DHT‐derived measures in clinical trials, leading to confusion regarding the evidence required to support these tools' use in drug development. There is a need to amend definitions and create clear evidentiary requirements to support broad adoption of these new and innovative tools. The biopharma industry, the technology sector, consulting businesses, academic researchers, and regulators need a dialogue via multi‐stakeholder collaborations to clarify questions around DHT‐derived measures, to unify definitions, and to create the foundations for evidentiary package requirements, providing a path forward to predictable results.